2017
DOI: 10.2459/jcm.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia as an independent risk factor for major cardiovascular events

Abstract: Hyperuricemia was shown to be a strong independent risk factor for MACE and should be included in cardiovascular prevention strategies. Whether hypouricemic drugs can decrease cardiovascular disease risk warrants further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 51 publications
0
21
0
3
Order By: Relevance
“…Confounder-adjusted stepwise linear regression revealed SUA, age, creatinine, glucose, and systolic blood pressure as independent predictors of MACE. Diastolic blood pressure and creatinine were independently correlated with SUA in the entire population, diastolic blood pressure only in men, and BMI, creatinine, age, and C3 in women 30 .…”
Section: Recent Advancesmentioning
confidence: 86%
See 1 more Smart Citation
“…Confounder-adjusted stepwise linear regression revealed SUA, age, creatinine, glucose, and systolic blood pressure as independent predictors of MACE. Diastolic blood pressure and creatinine were independently correlated with SUA in the entire population, diastolic blood pressure only in men, and BMI, creatinine, age, and C3 in women 30 .…”
Section: Recent Advancesmentioning
confidence: 86%
“…Hyperuricemia was shown to be a strong independent risk factor for major cardiovascular events (MACE) in a study that collected baseline clinical data through a 1998/1999 longitudinal survey as part of the Valle dell'Irno Prevenzione Project, and evaluated MACE incidence after 10 years 30 . A total of 1,175 patients (aged 25-74 years, 50% men) completed the study.…”
Section: Recent Advancesmentioning
confidence: 99%
“…Hyperuricemia is an illness caused by increased concentration of serum uric acid (> 420 μmol/l in men and > 358 μmol/l in premenopausal women) [14,15]. Gout is the most common inflammatory arthritis caused by the formation and deposition of monosodium urate (MSU) crystals among hyperuricemia patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that hyperuricemia increases the risk for cardiovascular diseases and mortality [1,2]. Chronic kidney disease (CKD) is also a risk for cardiovascular events and premature death [3].…”
Section: Introductionmentioning
confidence: 99%